Benney–Lin and Kawahara equations: a detailed study through Lie symmetries and Painlevé analysis. (5th September 2019) - Paliathanasis, Andronikos
Abstract: We perform a detailed study on the integrability of the Benney–Lin and KdV-Kawahara equations by using the Lie symmetry analysis and the singularity analysis. We find that the equations under our consideration admit integrable traveling-wave solutions. The singularity analysis is applied for the partial differential equations and the generic algebraic solution is presented.